Designing a model to improve the behavior of Iranian handicrafts e-commerce customers by increasing customer trust - mohsen seidi; Fataneh Alizadeh Meshkani; Ahmad Sardari; Abdullah Naami (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to design a model for improving the behavior of Iranian handicrafts e-commerce customers with the approach of improving customer trust. According to its purpose, the research method is applicable, and mixed (qualitative-quantitative) in terms of its implementation, and descriptive-exploratory in terms of data collection in the qualitative part. The statistical population of the research in the qualitative part includes 19 Iranian experts, including university professors in the fields of marketing management, handicrafts and senior managers of companies that export handicraft products, who through non-random sampling in the form of snowballs, were selected for interviews. The statistical population in the quantitative section includes 11 Iranian university professors in the fields of marketing management, handicrafts and senior managers of companies that export handicraft products, who were selected using non-probability sampling. A semi-structured interview was used to collect information in the qualitative section. To analyze the data in the qualitative part, first, content analysis was used to code the interviews, and in the quantitative part of the research, the self-interaction matrix was used for interpretive structural modeling (ISM). In the qualitative section, 16 sub-themes and seven main themes (indices) were extracted. In the quantitative part, a four-level model was obtained, and the most effective indicator of this model is electronic communication and interaction with customers. Also, its most effective indicator at the seventh level is confidence in purchasing. Therefore, 5 other criteria also play the role of interface factors in this model. Extended Abstract Introduction Today, advances in science and technology and the development of new technologies have created new competitive conditions for production and service organizations, so that quality and customer satisfaction and trust are the most important factors in global competition. Attracting and retaining customers in an organization is a category that is affected by various factors and conditions inside and outside the organization, the importance of which varies according to the type of organization and from one organization to another (Nguyen et al, 2020). Trust is defined as the trust of one party (trustee) to another person (trusted or trusted third party) (Yeon et al, 2019). Trust plays an important role in interactions and is important for companies and for developing relationships with consumers (Astono, 2021). Trust is the consumer's belief that the transaction will be carried out according to the plan. The way customers think about trust can be one-dimensional or multi-dimensional (Papas, 2018). On the other hand, in the late 1990s, the Internet promoted the formation of e-commerce, and the development of information technology in the middle years has caused the rapid development of e-commerce in the past 20 years (Baylok, 2021). E-commerce and information technology (IT) have a positive relationship. E-commerce and information technology are measured by evaluating the value of their business; the more the company gains positive value and trust, the more buyers it attracts (Alam & Osly, 2021). Electronic commerce is a set of technologies, applications, and business processes that connect companies, consumers, and communities through electronic transactions and electronic commerce of goods, services, and information (Rafiah, 2019). Based on this, the current research is looking for an answer to this question: What is the model for improving the behavior of Iranian handicrafts e-commerce customers with the approach of improving customer trust? Theoretical Framework Customer trust There are many definitions about trust. The multiplicity of definitions of trust in the theoretical texts of the subject probably originates from two reasons; first, trust is an abstract concept and sometimes it is synonymous with concepts such as authenticity, trustworthiness, or reliability. Second, trust is a multifaceted concept that has different perceptual, sensory and behavioral dimensions (Latifi & Momenkashani, 2014).